Exploring Identity Issues in British Men’s Magazines’ Problem Pages: A Cultural Studies Perspective - De Gregorio Godeo, Eduardo (Miscelánea: A Journal of English and American Studies, 2006)
Focusing on problem pages as a genre, this paper casts light on the varied subject positions or images of masculinity constructed in British men’s magazines (FHM, GQ, Later, Maxim, Men’s Health, Sky Magazine and ZM) at the end of the nineties. After theorizing the notion of ‘identity’ from a cultural studies perspective, and exploring men’s magazines as an arena for the articulation of masculinities in contemporary UK, men’s lifestyle magazines’ problem columns are examined in relation to the enduring presence of so-called ‘newmannism’ and ‘laddishness’ as major masculine subject positions made available to the magazines’ consumers. Rather than attempting to demonstrate any new changes in men’s subjectivities at the end of the twentieth century, the emphasis of this study is on showing how, contrary to a widely held view among men’s magazines analysts, newmannism did not fade away with the emergence of laddishness in the early nineties, but both subject positions were still very much alive at the end of the nineties. Through an analysis of illustrative examples, this contribution substantiates how the act of reading such a cultural artefact as men’s magazines’ problem pages provides male readers with access to masculine subject positions, no matter whether they are subsequently taken up or resisted.
Keywords: Britain; Cultural studies; Identity; 'Laddishness'; Masculinity; Men's magazines; 'Newmannism'; Problem pages; Subject positions